Fermented foods and beverages of the world - Tamang, Jyoti Prakash; Kailasapathy, Kasipathy (Food science and technology (Taylor & Francis), 2010)
Did you know? It's estimated that fermentation practices have been around since as early as 6000 BC, when wine was first being made in Caucasus and Mesopotamia. Today, there are roughly 5000 varieties of fermented foods and beverages prepared and consumed worldwide, which accounts for between five and forty percent of daily meals. Fermented Foods and Beverages of the World is an up-to-date review on fermentation practices, covering its storied past, cultural aspects, microbiology, biochemistry, nutrition, and functionality. With contributions from 24 seasoned fermentation authorities, this book begins with a concise introduction to food fermentation - one of the oldest biotechnological processes - including its history and global varieties. After covering the various preparation techniques and culinary methods, the book addresses the microbiology-phenotypic and genotypic characterizations, the identifications of functional microorganisms, the functional and technological properties, and issues related to food safety. The book also explores the functional properties of fermentation, how it improves product shelf life, ensures food safety, enriches nutritional supplements, and increases the probiotic functions in some foods. The rising popularity of probiotic and prebiotic foods and the health benefits they are known for are also discussed. Covering many undocumented minor or lesser-known ethnic fermented products, Fermented Foods and Beverages of the World is an all-in-one guide to global fermentation practices and consumption behaviors.